(untitled) (Journal of humanities and social sciences exploratio, 2026)
Against the backdrop of deepening globalization and cultural exchange, the musical—an integrated performing art that combines music, drama, dance, and stage art—has gradually become an important indicator of a country’s cultural industry and artistic innovation. China and South Korea, both belonging to the East Asian cultural sphere, share similarities in historical traditions and aesthetic psychology; however, they have followed different paths in the development history, artistic characteristics, and industrial models of musicals. This study takes representative early Chinese and Korean musicals as research subjects and employs literature review, comparative analysis, and case study methods to systematically examine the artistic characteristics of early musicals in the two countries, revealing both their commonalities and differences.The findings show that musicals in both countries have undergone the developmental stages of “introduction of foreign culture—local absorption—integration and innovation,” yet their specific trajectories differ significantly. Chinese musicals began in the 1980s and, after stages of introduction and localization, have gradually moved toward original creation and industrialization, and are still in the process of improving their industrial system and exploring artistic language. In contrast, since the introduction of musicals in the 1960s, South Korea has developed through a parallel model of original productions, licensed imports, and translated adaptations, forming a relatively mature industry with well-established systems in market operation, professional training, and international collaboration.Overall, the development of musicals in China and South Korea not only reflects the localization of foreign art forms within the East Asian context but also demonstrates distinct developmental paths shaped by different socio-cultural environments and industrial mechanisms, providing valuable references for the local creation and international dissemination of Chinese musicals.